1
9, 13, 17, 21, 25 b 4, 9, 16, 25, 36 c
2, 4, 8, 16, 32 d ,
,
,
,
e
−1, 4, 21,
56, 115 f ,
, 0, −
, −
g
,
,
,
,
h
16, 8, 4, 2, 1
|
|
|
2 a un = 3n + 1 |
b un = 7n − 7 |
c un = 18 − 2n |
a = 3, b = 1
|
a = 7, b = −7 |
a = −2, b = 18 |
d un = 1.3n − 0.9 |
e un = 117 − 17n |
f un = 8n − 21 |
a = 1.3, b = −0.9
3 possible answers are
|
a = −17, b = 117 |
a = 8, b = −21 |
a 5n − 4
|
b 3n |
c 2n2 |
d
× 2n
e 33 −
11n f (n − 1)3
g
n2 + 3 h n i
2n −
1
2 1n+
4 a u3 = c + 3 = 11 ∴ c = 8
b u6 = 8 + 34 = 89
5 a u4 = 4(8 + k) = 32 + 4k u6 = 6(12 + k) = 72 + 6k ∴ 72 + 6k = 2(32 + 4k) − 2
72 + 6k = 62 + 8k
k = 5
b un = n(2n + 5) = 2n2 + 5n un − 1 = (n − 1)[2(n − 1) + 5] = (n − 1)(2n + 3) = 2n2 + n − 3
∴ un − un − 1 = (2n2 + 5n) − (2n2 + n − 3) = 4n + 3
6 a u1 = k − 3 u2 = k2 − 3
∴ k − 3 + k2 − 3 = 0 k2 + k − 6 = 0 (k + 3)(k − 2) = 0 k = −3 or 2
b k = −3 ⇒ u5 = (−3)5 − 3 = −243 − 3 = −246
k = 2 ⇒ u5 = 25 − 3 = 32 − 3 = 29
7 a 3, 7, 11, 15 b 2, 7, 22, 67
c −2, 1, 7, 19 d 5, 2, 5, 2
e −1, 14, −46, 194 f 10, 3, 2.3, 2.23
g
6, −1, 1 ,
h
0,
,
,
8 possible answers are
|
|
|
a un+1 = un + 4, u1 = 5
|
b un+1 = 3un, u1 = 1 |
c un+1 = un − 18, u1 = 62 |
d
un+1 = un, u1
= 120 e un+1 = 2un
+ 1, u1 = 4 f un+1
= 4un −
1, u1 = 1
9
a −3
= −4a
+ b b 8 = b c 4 = a + b
−1 = −3a + b 4 = 8a + b 3 = 4a + b
subtracting, 2 = a a = − , b =
8 subtracting, 1 =
a a = 2, b = 5 a
=
,
b =
10 a u2 = 4 + 3k b u2 = 2k + 5
u3 = 4(4 + 3k) + 3k = 16 + 15k u3 = k(2k + 5) + 5 = 2k2 + 5k + 5
c u2 = 4k − k = 3k d u2 = 2 + k
u3 = 4(3k) − k = 11k u3 = 2 − k(2 + k) = 2 − 2k − k2
e u2
= 4 f
u2 = 3 61k3 +3k3
= 3 64k3 = 4k
k
u3 = 4 ÷ k =
42 u3 = 3 61k3 +64k3
= 3 125k3 = 5k k k
11
a u2 = (k + 6) u3
=
[k
+
(k
+ 6)] =
(5k + 18) b
(5k
+ 18) = 7 k = 2
u4
= (2
+ 21) = 11
12
a u4 = 30 −
2 = 28 b u4 = + 2 = 5
10
= 3u2 −
2 ∴ u2
= 4 5 = u2 +
2 ∴ u2
= 4
4 =
3u1 −
2 ∴ u1
= 2 4 = u1 +
2
2
c
u4 = 0.2 ×
1.2 = 0.24 d u
−0.2 = 0.2(1 − u2)
∴ u2
= 2 1 = = 4
2 =
0.2(1 − u1)
∴ u1
= −9 4 = =
64
13 a u5 = 2 + 4c = 30 ∴ c = 7
b sequence is 2, 9, 16, 23, 30, …
∴ un = 7n − 5
14 a u2 = 3(−4 − k) = −12 − 3k u3 = 3[(−12 − 3k) − k] = −36 − 12k
b −36 − 12k = 7(−12 − 3k) + 3
9k = −45 k = −5
c u3 = −36 + 60 = 24 ∴ u4 = 3(24 + 5) = 87
15 a t2 = 1.5k + 2
t3 = k(1.5k + 2) + 2 = 1.5k2 + 2k + 2
b 1.5k2 + 2k + 2 = 12
3k2 + 4k − 20 = 0 (3k
+ 10)(k −
2) = 0 k = −3 , 2
|
|
|
|
|
1 |
|
d = 6 |
b d = −3 c |
d = 2.3 |
|
|
u40 = 4 + (39 × 6) = 238 |
u40 = 30 + (39 × −3) = −87 |
u40 = 8.9 + (39 × 2.3) = 98.6 |
2
a a = 7, d = 2 b a = , d
=
c
a = 17, d = −8
un = 7 + 2(n
− 1) = 5 +
2n un = +
(n −
1) = −
+
n un = 17 − 8(n − 1) = 25 − 8n
3
a a = 8, d = 4, n = 30 b a
= 60, d = −7,
n = 30 c a = 7 , d = 1
, n
= 30
S30
= [16 + (29 ×
4)] S30 =
[120 + (29 × −7)] S30
=
[14
+ (29 × 1 )]
= 1980
|
|
|
|
|
|
|
|
= −1245 |
|
|
|
|
|
|
= 870 |
4
a S20 = (60 + 136) b
S32 =
(100 + 84.5) c S17
=
[28 + (−20)]
= 1960
|
|
|
|
|
|
|
|
= 2952 |
|
|
|
|
|
|
|
= 68 |
5
a S48 = [4 + (47 × 9)] b S36
=
[200 + (35 ×
−5)] c
S55 =
[38 + (54 ×
13)]
|
= 10 248 |
|
|
|
= 450 |
|
= 20 350 |
6 |
a 8 + 3(n − 1) = 65 |
|
|
|
b 3.4 + 1.2(n − 1) = 23.8 |
|
c 22 − 8(n − 1) = −226 |
|
n = 20 |
|
|
|
n = 18 |
|
n = 32 |
S20
= (8 + 65) S18
=
(3.4 + 23.8) S32
=
[22 + (−226)]
|
= 730 |
|
|
|
|
|
|
= 244.8 |
= −3264 |
7 |
a a = 21 |
|
|
|
|
|
|
8 |
n = 1, first term = 7 + 16 = 23 |
|
21 + 2d = 27 |
|
|
|
|
|
|
|
d = 7 |
∴ d = 3 S35
= [46 + (34 ×
7)] = 4970
b
S40 = [42 + (39 ×
3)] = 3180
|
|
|
|
|
|
|
|
|
9 |
a a + d = 13 |
|
|
|
|
|
10 |
a a + 2d = 72 |
|
a + 4d = 46 |
|
|
|
|
|
|
a + 7d = 37 |
|
b subtracting, 3d = 33 |
|
|
|
|
|
|
subtracting, 5d = −35 |
|
d = 11 |
|
|
|
|
|
|
d = −7 |
|
sub. a = 2 |
|
|
|
|
|
|
sub. a = 86 |
c
u40 = 2 + (39 ×
11) = 431 b
S25 = [172 + (24 ×
−7)] = 50
11 a a + 4d = 23 (1) 12 a Sn = 1 + 2 + 3 + … + (n − 1) + n
(2a
+ 9d) = 240 ⇒
2a + 9d = 48 write in reverse
2 × (1) ⇒ 2a + 8d = 46 Sn = n + (n − 1) + … + 3 + 2 + 1
subtracting, d = 2 adding, 2Sn = n × (n + 1)
sub. a = 15 Sn
= n(n
+ 1) b S60 =
[30 + (59 × 2)] = 4440 b
= S100 −
S29
=
× 100 × 101 −
× 29 × 30
= 5050 − 435 = 4615
13 a 5 + 7 + 9 + 11 + 13 b 15 + 12 + 9 + 6 + 3 + 0 − 3 − 6 − 9
c 15 + 19 + 23 + 27 + 31 + 35 + 39
d
4 + 4 + 3
+ 3 + 2
+ 2 + 1
+ 1
14 a AP: a = 4, b AP: a = 88, c AP: a = 19, d AP: a = 3, l = 61, n = 20 l = 0, n = 45 l = 127, n = 28 l = 13, n = 41
S20 = (4
+ 61) S45 =
(88 + 0) S28
=
(19 + 127) S41 =
(3
+ 13) = 650 =
1980 = 2044 =
328
15 AP: a = −2, l = 4n − 6 16 a AP: a = 2, l = 160, n = 80
Sn = 6)]
= 720 S80 =
(2
+ 160) = 6480
∴
n(4n −
8) = 1440 b
AP: a = 3, l = 198, n = 66 n2 − 2n − 360 = 0 S66
= (3 + 198) = 6633 (n +
18)(n −
20) = 0 c
AP: a = 30, l = 300, d = 6
n > 0 ∴ n = 20 30 + 6(n − 1) = 300 ∴ n = 46
S46
= (30 + 300) = 7590
17 a a + (9 × −11) = 101 18 a a = 17, 17 + 4d = 27 ∴ d = 2.5
a = 200 b 17 + 2.5(r − 1) = 132
b
S30 = [400 + (29 ×
−11)] =
1215 r = 47
c
S47 = (17 + 132) = 3501.5
19 a (2a + 5d)
= 213 ⇒
2a + 5d = 71 20 a S8 = (2 × 82)
+ (5 × 8) =
168
(2a + 9d) = 295 ⇒ 2a + 9d
= 59 b S7 = (2 × 72)
+ (5 × 7) =
133 subtracting, 4d = −12
u8
= S8 −
S7 = 35 d
= −3 c
Sn −
1 = 2(n −
1)2 + 5(n −
1) sub. a = 43 =
2n2 + n −
3
b
43 −
3(n −
1) > 0 un
= Sn −
Sn −
1 n < 15 positive terms =
(2n2 + 5n) −
(2n2 + n −
3)
c max Sn when n = 15 = 4n + 3
S15 = [86
+ (14 × −3)] = 330
21 a (2k + 3) − (k + 2) = (4k − 2) − (2k + 3) 22 a 2t − (5 − t) = (6t − 3) − 2t
k + 1 = 2k − 5 3t − 5 = 4t − 3
k = 6 t = −2
b a = 8, a + d
= 15 ∴ d
= 7 b u5
= 7, u6 = −4
∴ d
= −11 S25
= [16 + (24 ×
7)] = 2300 a
+ (4 × −11) = 7 ∴ a = 51
S [102
+ (17 × −11)] = −765
1 a
+ 2d = −10
(1) 2 a a + 2d
=
(2a + 7d) = 16 ⇒ 2a + 7d
= 4 a + 6d
= 2
2 ×
(1) ⇒
2a + 4d = −20
subtracting, 4d = 1
subtracting,
3d = 24 d
=
d
= 8 sub.
a =
sub. a = −26 b
Sn = n2 [ 16
+ (n
− 1)] b
−26 + 8(n
− 1) >
300 =
n[4
+ 9(n −
1)] n >
smallest n = 42 =
n(9n
− 5) [
k =
]
3 a
(2a
+ 8d) = 126 4 a
(5k + 3) −
(7k −
1) = (4k + 1) −
(5k + 3)
9(a + 4d) = 126 −2k + 4 = −k − 2
a + 4d = 14 k = 6
b
(2a + 14d) = 277.5 b
given terms = 41, 33, 25
a + 7d = 18.5 d = −8
subtracting, 3d = 4.5 smallest +ve term = 25 + (3 × −8) = 1
d = 1.5 c consider series of +ve terms in reverse
sub. a = 8 a = 1, d = 8
c
S32 = [16 + (31 ×
1.5)] = 1000 Sr
= 2r [2 + 8(r − 1)] = r(4r
− 3)
|
|
|
|
|
|
|
|
5 |
a AP: a = 4, l = 120, n = 30 |
|
|
|
|
6 |
a 500 + (7 × 40) = £780 |
S (4 +
120) = 1860 b AP: a = 500, d
= 40
30 b i = ∑ 4r + 30 = 1890 r=1 |
|
|
|
|
|
|
Sn = n2 [1000 + 40(n − 1)] = 20n(n + 24) |
30 ii = 2 ×∑ 4r − (30 × 5) r=1 |
|
|
|
|
|
|
c AP: a = 400, d = 60 |
=
(2 × 1860) − 150 = 3570 Sn
= 1)] = 10n(3n + 37)
∴ 20n(n + 24) = 10n(3n + 37) n ≠ 0 ∴ 2(n + 24) = (3n + 37)
n = 11 ∴ 11 years
7 a
Sn = 2 + 4 + 6 + … + (2n − 2) + 2n 8
a Sn = a + (n − 1)d]
write in reverse b
Sa + d
Sn = 2n + (2n
− 2) + … +
6 + 4 + 2 Sa
+ 5d) = 6a + 15d adding, 2Sn = n
× (2n
+ 2) S
a
+ 7d) = 8a + 28d
Sn = n(n + 1) |
|
|
|
|
2(S6 − S2) = 2[(6a + 15d) − (2a + d)] |
b integers 200 to 800, AP: n = 601 |
|
|
|
|
= 2(4a + 14d) |
S601 = (200
+ 800) = 300 500 =
8a + 28d = S8
integers 200 to 800 divisible by 4 c for +ve terms 40 − 3(n − 1) > 0
AP: a = 200, l
= 800 n
< 14 terms
200
+ 4(n −
1) = 800 ⇒
n = 151 [80 + (13 × −3)] = 287
S151 = (200
+ 800) = 75 500
required sum = 300 500 − 75 500
= 225 000
9 a i u4 − u1
= x + 3 10
Sa + 19d) = 20a + 190d
u7 = u4 + (x + 3)
= 3x + 6 S
a
+ 29d) = 30a + 435d ii 3d = x
+ 3 S30
− S20
= 10a + 245d d =
x + 1 ∴ 20a +
190d = 10a + 245d iii S10 =
[2x
+ 9(
x + 1)] 10a
= 55d
= 5[2x + 3x
+ 9] = 25x + 45 2a
= 11d b x + 19( x + 1) = 52 ∴ a : d
= 11 : 2
3x + 19x + 57 = 156 x
= =
or 4
11 a S6 = 12(16 − 6) = 120 12
a i 2400 + (5 ×
250) = 3650 S5 = 10(16 −
5) = 110 ii
AP: a = 2400, d = 250 u6 = S6
− S5
= 10 S10
= [4800 + (9 ×
250)] b Sn = 2n(16 − n) = 32n
− 2n2
=
35 250 Sn
−
1 = 2(n −
1)[16 − (n
− 1)] b
AP: a = 2400, d = C
= 2(n − 1)(17 − n) [4800
+ (9 × C)]
= 40 000 =
−2n2
+ 36n −
34 C
=
= 356 (nearest unit)
un = Sn − Sn − 1
= (32n − 2n2) − (−2n2 + 36n − 34)
= 34 − 4n
c un − 1 = 34 − 4(n − 1) = 38 − 4n un − un − 1 = (34 − 4n) − (38 − 4n) = −4 un − un − 1 constant ∴ arithmetic series
13 a let common difference be d
Sr = a + (a + d) + (a + 2d) + … + (l − 2d) + (l − d) + l write in reverse
Sr = l + (l − d) + (l − 2d) + … + (a + 2d) + (a + d) + a
adding, 2Sr = r × (a + l)
Sr
= r(a
+ l)
b n = 18, l = 68, S18 = 153
∴
153 = (a + 68) a
= 17 − 68 =
−51
|
|
|
|
|
|
|
|
1 |
a + d = 40, a + 4d = 121 |
|
|
|
|
2 |
a 3, 7, 11, 15, 19 |
|
subtracting, 3d = 81 |
|
|
|
|
|
b AP: a = 3, d = 4, n = 20 |
d
= 27 S20 = [6
+ (19 × 4)]
sub. a = 13 = 820
b S25 = [26
+ (24 ×
27)] = 8425
3 a (2t − 5) −
t = 8.6 −
(2t −
5) 4 a Sn
= (n + 1) t = 6.2 b
= S400 −
S199
b
u1 = 6.2, u2 = 12.4 − 5 = 7.4 = × 400 × 401
× 199 × 200 a =
6.2, d = 7.4 −
6.2 = 1.2 =
80 200 − 19 900 = 60 300 u16 =
6.2 + (15 ×
1.2) = 24.2 c
(N + 1) = 4950
c
S20 = [12.4 + (19 × 1.2)] = 352 N
2 + N −
9900 = 0
(N + 100)(N − 99) = 0
N > 0 ∴ N = 99
5 a u2 = k
+ 1 6
a AP: a = 3, d = 3 u3 = k
+ (k + 1)2 = k2 + 3k + 1 500
÷ 3 = n
= 166 b k2 + 3k + 1 = 1 S
[6
+ (165 ×
3)]
k(k + 3) = 0 = 41 583
k ≠
0 ∴ k
= −3 b
AP: a = 14, l = 99, n = 18 c u25
= 1 S18
= (14 + 99)
u1 = 1 ⇒ u3 = 1 = 1017
∴ un = 1 for all odd values of n
7 a Sn = a + (a + d) + (a + 2d) + … 8 t2 = 4 + 2k
+ [a + (n − 2)d] + [a + (n − 1)d] t3 = 4 − k(4 + 2k) write in reverse ∴ 4 − 4k − 2k2 = 3
Sn = [a + (n − 1)d] + [a + (n − 2)d] + … 2k2 + 4k − 1 = 0
+ (a + 2d)
+ (a + d) + a k
= adding 2Sn = n
× {a
+ [a + (n −
1)d]} k > 0
Sn
=
a + (n − 1)d] b
S
2 + (25 ×
6)] = 1924
S 2 +
(26 × 6)] =
2079
∴ largest n = 26
9 a = 6 + (19 × 3) = 63 10
a = 3 ×
570 = 1710 b Sn = 1)] = 270 b
= 570 + (2 ×
30) = 630 ∴
n(3n + 9) = 540 c
= 570 + (
×
30 × 31) =
1035 n2 + 3n − 180 = 0 (n
+ 15)(n −
12) = 0 n > 0 ∴
n = 12
11 a 2 years = 8 × 3 months 12
AP: a = 80, d = −3,
n = 45 total = 3 ×
S8 [AP: a = 40, d = 2] S45
= [160 + (44 ×
−3)] = 630
= 3 × [80
+ (7 × 2)]
= 3 × 376 = £1128 b n years = 4n × 3 months total = 3 × S4n
= 3 × 42n {80 + [(4n − 1) × 2]}
= 6n(80 + 8n − 2)
= 12n(4n + 39)
13 a a + 2d = 298, a + 7d = 263 14 a AP: a = 10, d = 6 subtracting, 5d = −35 Sn = n2 [20 + 6(n − 1)]
d = −7 = n(3n + 7)
b sub. a =
312 b
S2n = 2n[(3 ×
2n) + 7] 312 −
7(n −
1) > 0 =
12n2 + 14n n 45 positive terms
required sum = S2n
− Sn
c max Sn when n = 45 =
(12n2 + 14n) −
(3n2 + 7n)
S45 = [624
+ (44 × −7)] = 7110 =
9n2 + 7n = n(9n + 7)
15 a u2 = k2 − 2, u4 = k4 − 4 16 a (4k − 2) − (k + 4) = (k2 − 2) − (4k − 2)
∴ k2
− 2 + k4
− 4 = 6 3k
− 6 = k2
− 4k
k4 + k2 − 12 = 0 k2
− 7k
+ 6 = 0 (k2 + 4)(k2
− 3) = 0 b
(k −
1)(k −
6) = 0 k2 = −4
[no solutions] or 3 k
= 1 or 6 k > 0 ∴
k = 3 d
= 3k −
6 b u1 = 3 −
1 d
> 0 ∴ k
= 6
u3 = ( 3 )3 − 3 = 3( 3 − 1) = 3u1 a = 10, d = 12
u15 = 10 + (14 × 12) = 178
Материалы на данной страницы взяты из открытых источников либо размещены пользователем в соответствии с договором-офертой сайта. Вы можете сообщить о нарушении.